2021
DOI: 10.3389/fmicb.2021.791489
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Serum Levels of the Nucleocapsid Antigen of SARS-CoV-2 With the Diagnosis, Disease Severity, and Antibody Titers in Patients With COVID-19: A Retrospective Cross-Sectional Study

Abstract: Background: Several types of laboratory tests for COVID-19 have been established to date; however, the clinical significance of the serum SARS-CoV-2 nucleocapsid (N) antigen levels remains to be fully elucidated. In the present study, we attempted to elucidate the usefulness and clinical significance of the serum N antigen levels.Methods: We measured the serum N antigen levels in 391 serum samples collected from symptomatic patients with a confirmed diagnosis of COVID-19 and 96 serum samples collected from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
2
13
1
Order By: Relevance
“…We next examined whether the NK degranulation measured ex vivo correlated with markers of disease severity in vivo . Plasma SARS-CoV-2 plasma nucleocapsid (N) antigen load correlates with disease severity ( 21 23 ). Therefore, we measured the N-antigen load in the plasma samples using an ultrasensitive Simoa SARS-CoV-2 N-protein assay and correlated it with NK direct cytolytic and ADCC activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next examined whether the NK degranulation measured ex vivo correlated with markers of disease severity in vivo . Plasma SARS-CoV-2 plasma nucleocapsid (N) antigen load correlates with disease severity ( 21 23 ). Therefore, we measured the N-antigen load in the plasma samples using an ultrasensitive Simoa SARS-CoV-2 N-protein assay and correlated it with NK direct cytolytic and ADCC activities.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, given our results demonstrating sex-dependent differences in Siglec expression on NK cells and NK cytotoxic activities, larger studies are needed to examine the impact of sex/gender (and other demographic and clinical features) on the relationship between Siglec expression and antiviral immune functions. In addition, we have used the plasma N-antigen load as a simple blood-based biomarker of SARS-CoV-2 infection severity ( 21 23 ); however, further examinations are needed to establish links between NK functionality and upper-respiratory viral load. Second, regarding the NK cytotoxicity assays, it will be critical in future studies to explore the cytotoxicity of NK cells against primary epithelial cells infected with different variants of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…The biological basis of NCP antigenemia is still ill-defined. Plasma NCP antigenemia was found not to correlate with mucosal Ct values [8]. However, it is unresolved whether NCP antigen in plasma reflects ongoing systemic viral replication [12], or rather dissemination from the respiratory tract [10].…”
Section: Discussionmentioning
confidence: 99%
“…A high level of serum NCP antigen was consistently found to be associated with serious illness [4][5][6][7]. It was suggested that the serum NCP antigen level may serve as an early biomarker for predicting the maximum disease grade of severe COVID-19, using NCP antigenemia as a tool for allocation of ICU options on admission [8]. However, some patients progress to more severe disease not before the second week of Covid-19; for those patients, no biomarker has been established yet.…”
Section: Introductionmentioning
confidence: 99%
“…In COVID-19 treatment, RT-PCR tests and antigen tests are not suitable for the proper assessment of COVID-19 severity. PCR tests and antigen tests for the SARS-CoV-2 viral genome from saliva or nasopharyngeal swab have no correlation with COVID-19 severity [ 21 , 22 , 23 , 24 ]. From our study, the elevations of t 6 A and ms 2 t 6 A in serum correlated with the severity and recovery of infection.…”
Section: Discussionmentioning
confidence: 99%